Corona Virus Disease 2019 (COVID-19) as a System-Level Infectious Disease With Distinct Sex Disparities - Emadi-Baygi, Modjtaba; Ehsanifard, Mahsa; Afrashtehpour, Najmeh; Norouzi, Mahnaz; Joz-Abbasalian, Zahra (Frontiers in Immunology, 2021)
The current global pandemic of the Severe Acute Respiratory Syndrome CoronaVirus 2 (SARS-CoV-2) causing COVID-19, has infected millions of people and continues to pose a threat to many more. Angiotensin-Converting Enzyme 2 (ACE2) is an important player of the Renin-Angiotensin System (RAS) expressed on the surface of the lung, heart, kidney, neurons, and endothelial cells, which mediates SARS-CoV-2 entry into the host cells. The cytokine storms of COVID-19 arise from the large recruitment of immune cells because of the dis-synchronized hyperactive immune system, lead to many abnormalities including hyper-inflammation, endotheliopathy, and hypercoagulability that produce multi-organ dysfunction and increased the risk of arterial and venous thrombosis resulting in more severe illness and mortality. We discuss the aberrated interconnectedness and forthcoming crosstalks between immunity, the endothelium, and coagulation, as well as how sex disparities affect the severity and outcome of COVID-19 and harm men especially. Further, our conceptual framework may help to explain why persistent symptoms, such as reduced physical fitness and fatigue during long COVID, may be rooted in the clotting system.